Wage inequality in Europe: The institutional and economic factors supporting workers - Wouter Zwysen (European Trade Union Institute (ETUI), 2024)
Much of the literature on wage inequality describes increases in wage inequality over time driven by seemingly unstoppable forces of technological change and globalisation, widening the gaps between workers and disadvantaging the lower paid. At the same time institutional protection has continued to decline. It is, however, not as clear that wage inequality is actually on a constant rise everywhere. First, the evidence from Europe is generally more mixed with an overall decline in wage inequality since the early 2000s and substantial variation between countries. Second, even in the United States there has recently been a reversal in the trend of rising wage inequality, likely to have been driven by the greater bargaining power of lower-paid workers. This paper considers in detail the role played by the institutional as well as the economic factors that shape wage floors and protect workers at the low end of the wage distribution. Using detailed data from EU-SILC from 2007 to 2021, enriched with contextual data, it shows that wage inequality has indeed on average declined across the EU (1). This is primarily due to convergence between countries. In line with expectations, strong institutional support, such as statutory minimum wages with greater bite and a higher collective bargaining coverage rate, are associated with lower inequality and a better position for vulnerable workers (2). Multilevel analysis indicates that, over time, changes in these institutional settings and in the demand for workers - affecting their bargaining power - affect inequality at the country-industry level (3). This paper provides insights into aspects of European labour institutions and labour market factors that affect inequality and shows that wages, particularly at the bottom of the wage distribution, are supported by institutional factors through the state or collective actors, as well as affected by the demand for labour.
Keywords: 330; Wage structure; Institutional infrastructure; EU countries; Lohnstruktur; Institutionelle Infrastruktur; EU-Staaten